AhR and HIF-1α Signaling Pathways in Benign Meningioma under Hypoxia - Maria L. Perepechaeva; Lyubov S. Klyushova; Alevtina Y. Grishanova (International Journal of Cell Biology)
The role of hypoxia in benign meningiomas is less clear than that in the malignant meningiomas. Hypoxia-induced transcription factor 1 subunit alpha (HIF-1α) and its downstream signaling pathways play a central role in the mechanism of hypoxia. HIF-1α forms a complex with the aryl hydrocarbon receptor nuclear translocator (ARNT) protein and can compete for ARNT with aryl hydrocarbon receptor (AhR). In this work, the status of HIF-1α- and AhR-dependent signaling pathways was investigated in World Health Organization (WHO) grade 1 meningioma and patient-derived tumor primary cell culture under hypoxic conditions. mRNA levels of HIF-1α, AhR, and of their target genes as well as of ARNT and nuclear receptor coactivator NCOA2 were determined in tumor tissues from patients in whom the tumor was promptly removed either with or without prior endovascular embolization. Using the patient-derived nonembolized tumor primary cell culture, the effects of a hypoxia mimetic cobalt chloride (CoCl2) and an activator of the AhR signaling pathway benzo(α)pyrene (B[a]P) on mRNA levels of HIF-1α, AhR, and their target genes were investigated. Our findings show active functioning of AhR signaling in meningioma tissue of patients with tumor embolization and crosstalk between HIF-1α and AhR signaling in meningeal cells under hypoxia.